The December 2016 extreme weather and particulate matter pollution episode in the Paris region (France). (15th December 2022) - Foret, G.; Michoud, V.; Kotthaus, S.; Petit, J.-E.; Baudic, A.; Siour, G.; Kim, Y.; Doussin, J.-F.; Dupont, J.-C.; Formenti, P.; Gaimoz, C.; Ghersi, V.; et al.
Highlights: Study of an intense winter episode of particulate pollution in the Paris region. Exceptional stagnant conditions explain the highest concentrations. Organic matter of local origin dominates the chemical composition of the particles with also a strong nitrate component from traffic. Significant values of oxidative potential are observed.